A low-flux state in IRAS 00521−7054 seen with NuSTAR and XMM–Newton: relativistic reflection and an ultrafast outflow. Issue 2 (16th January 2019) - Walton, D J; Nardini, E; Gallo, L C; Reynolds, M T; Ricci, C; Dauser, T; Fabian, A C; García, J A; Harrison, F A; Risaliti, G; Stern, D
ABSTRACT: We present results from a deep, coordinated XMM–Newton + NuSTAR observation of the Seyfert 2 galaxy IRAS 00521−7054. The NuSTAR data provide the first detection of this source in high-energy X-rays ( E > 10 keV), and the broad-band data show this to be a highly complex source which exhibits relativistic reflection from the inner accretion disc, further reprocessing by more distant material, neutral absorption, and evidence for ionized absorption in an extreme, ultrafast outflow (v out ∼ 0.4 c ). Based on lamppost disc reflection models, we find evidence that the central supermassive black hole is rapidly rotating ( a > 0.77), consistent with previous estimates from the profile of the relativistic iron line, and that the accretion disc is viewed at a fairly high inclination ( i ∼ 59°). Based on extensive simulations, we find the ultrafast outflow is detected at ∼4σ significance (or greater). We also estimate that the extreme outflow should be sufficient to power galaxy-scale feedback, and may even dominate the energetics of the total output from the system.